Parsing the Neural Mechanisms of Short-Term and Long-Term Associations in the Flanker Tasks: An ERP Analysis - Cheng, Wenwen; Huang, Qiao; Chen, Ying; Dai, Weipeng; Cui, Liyan; Shan, Sharui; Chen, Zhuoming; Zhou, Shu (Frontiers in Behavioral Neuroscience, 2021)
The neural mechanisms of cognitive conflicts within various flanker tasks are still unclear, which may be mixed with different effects of short-term associations and long-term associations. We applied a perceptual (color) flanker task and a symbolic (arrow) flanker task to 25 healthy young adults, while the event-related potentials (ERP) and behavioral performance were recorded. The former contains stimulus-stimulus conflict (SSC) of short-term memory (STM) associations, and the latter contains stimulus-response conflict (SRC) of long-term memory (LTM) associations. Both flanker tasks included congruent and incongruent conditions. The reaction time demonstrated the stimulus-response conflict effect in the arrow flanker task without the stimulus-stimulus conflict effect in the color flanker task. The ERP results showed SSC enhanced the frontocentral N2b without behavioral effects. And SRC increased the frontocentral P2 but decreased the centroparietal P3b with prolonged reaction time. In the comparison between both tasks, the color flanker task elicited both the centroparietal N2b/N300 and the frontocentral N400 and the arrow flanker task increased the occipital N1. Our findings provide new evidence that different neural mechanisms underlie conflict effects based on different types of memory associations.